Circulating mitochondrial cell-free DNA dynamics in patients with mycobacterial pulmonary infections: Potential for a novel biomarker of disease - Pan, Sheng-Wei; Syed, Rehan R.; Catanzaro, Donald G.; Ho, Mei-Lin; Shu, Chin-Chung; Tsai, Tsung-Yeh; Tseng, Yen-Han; Feng, Jia-Yih; Chen, Yuh-Min; Su, Wei-Juin; Catanzaro, Antonino; Rodwell, Timothy C. (Frontiers in Immunology, 2022)
Objectives: Human mitochondrial cell-free DNA (Mt-cfDNA) may serve as a useful biomarker for infectious processes. We investigated Mt-cfDNA dynamics in patients with pulmonary mycobacterial infections to determine if this novel biomarker could be used to differentiate disease states and severity. Methods: Patients with pulmonary tuberculosis (PTB), latent tuberculosis infection (LTBI), and nontuberculous mycobacterial-lung disease (NTM-LD) were enrolled at a tertiary care hospital in Taiwan between June 2018 and August 2021. Human Mt-cfDNA and nuclear-cfDNA (Nu-cfDNA) copy numbers were estimated by quantitative polymerase chain reaction. Variables associated with PTB and 2-month sputum culture-positivity, indicating poor treatment response, were assessed using logistic regression. Results: Among 97 patients with PTB, 64 with LTBI, and 51 with NTM-LD, Mt-cfDNA levels were higher in patients with PTB than in LTBI (p=0.001) or NTM-LD (p=0.006). In the Mycobacterium tuberculosis-infected population, Mt-cfDNA levels were highest in smear-positive PTB patients, followed by smear-negative PTB (p<0.001), and were lowest in LTBI persons (p=0.009). A Mt-cfDNA, but not Nu-cfDNA, level higher than the median helped differentiate culture-positive PTB from culture-negative PTB and LTBI (adjusted OR 2.430 [95% CI 1.139–5.186], p=0.022) and differentiate PTB from NTM-LD (adjusted OR 4.007 [1.382–12.031], p=0.011). Mt-cfDNA levels decreased after 2 months of treatment in PTB patients (p=0.010). A cutoff Mt-cfDNA level greater than 62.62 x 106 copies/μL-plasma was associated with a 10-fold risk of 2-month culture-positivity (adjusted OR 9.691 [1.046–89.813], p=0.046). Conclusion: Elevated Mt-cfDNA levels were associated with PTB disease and failed sputum conversion at 2 months in PTB patients, and decreased after treatment.